Perancangan Animasi Edukasi Bahasa Inggris Tingkat Dasar - Ispandi, Ispandi; Fakhriza, M Hilman (Universitas Pendidikan Ganesha, 2018)
With the development of technology, the role of educational applications in education is increasingly important. Almost at various levels of education, ranging from toddler age up to a higher level is used as an alternative medium of education and science penggettahuan. Various themes are taken increasingly diverse, including learning a foreign language, practice UAS (End Semester Exam), exercise UAN (National Final Examination), exercise SNCA (Selection of New Student Reception), kindergarten (kindergarten), elementary education (ElementarySchool). The application provides many facilities for educating the educators in providing knowledge and learning for their children outside of school education, books. With the above reasons pembelajaan module was created as a means of education for children who have aged 6-9 years to get to know a variety of English vocabulary that exist around them. In this paper the authors use a flash.